"DANCE, LAUGH, LEARN: THE ELEMENT APPEALS INFLUENCING TIK TOK FOLLOWER INTENTIONS": A CONCEPTUAL PAPER - Shammil bin Shabri,; Wan Hashridz Rizal bin Wan Abu Bakar,; Faiqah binti Ahmad Radzuan, (Journal of Islamic, Social, Economics and Development, 2023)
This conceptual paper explores the multifaceted dynamics influencing follower intentions on Tik Tok, a global cultural phenomenon in the realm of social media. The study investigates the interplay of perceived originality, quality, quantity, and humor as key elements shaping user engagement and behavior on the platform. The explosive growth of Tik Tok in Malaysia is examined, revealing its impact on the local digital landscape, particularly among the younger demographic. The research underscores the importance of perceived originality, demonstrating its role in captivating and retaining audience attention in a rapidly changing environment where trends evolve swiftly. Additionally, the study delves into the subjective yet critical factors of perceived quality, emphasizing the significance of high production standards, visual appeal, and authenticity in fostering positive attitudes among followers. The concept of perceived quantity is explored, highlighting the need for a strategic approach to content frequency to maintain audience interest without compromising quality. The inclusion of perceived humor as a driving element on Tik Tok is discussed, acknowledging its role in creating a hedonic experience and contributing to the formation of opinion leaders. The findings provide valuable insights for content producers, marketers, and academics, offering a deeper understanding of the intricacies that shape Tik Tok follower intentions amid the dynamic landscape of social media. As Tik Tok and related platforms continue to evolve, staying attuned to the delicate interplay of originality, quality, quantity, and humor becomes essential for navigating and thriving in this dynamic digital environment.